Marketing : real people, real choices - Solomon, Michael R. (Prentice Hall, 2000)
Making Marketing Decisions; Understanding and Identifying Markets; Creating and managing a Product: Goods and Services; Assigning Value to the Product. Delivering the product; Communicating about the Product.